2015
DOI: 10.1073/pnas.1509158112
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of inflammation and tissue damage in sickle cell model mice by Nrf2 activation

Abstract: Sickle cell disease (SCD) is an inherited disorder caused by a point mutation in the β-globin gene, leading to the production of abnormally shaped red blood cells. Sickle cells are prone to hemolysis and thereby release free heme into plasma, causing oxidative stress and inflammation that in turn result in damage to multiple organs. The transcription factor Nrf2 (nuclear factor erythroid 2-related factor 2) is a master regulator of the antioxidant cell-defense system. Here we show that constitutive Nrf2 activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 51 publications
10
67
0
Order By: Relevance
“…In summary, results from chronic DMF treatment illustrate that DMF induces HbF, improves Hb level, and modulates the proinflammatory state in SCD. This beneficial reduction in proinflammatory cytokines and markers of inflammation in SCD mice is in agreement with previously published studies in an SCD mouse model where Nrf2 is genetically activated by decreasing expression of Keap1 (28) or chronic treatment with DMF (34).…”
Section: Twice a Day [Bid]) And Subjected To Cbc Analysis Hematolosupporting
confidence: 92%
See 1 more Smart Citation
“…In summary, results from chronic DMF treatment illustrate that DMF induces HbF, improves Hb level, and modulates the proinflammatory state in SCD. This beneficial reduction in proinflammatory cytokines and markers of inflammation in SCD mice is in agreement with previously published studies in an SCD mouse model where Nrf2 is genetically activated by decreasing expression of Keap1 (28) or chronic treatment with DMF (34).…”
Section: Twice a Day [Bid]) And Subjected To Cbc Analysis Hematolosupporting
confidence: 92%
“…We used these SCD mice to study the ability of DMF to induce HbF and to induce cytoprotective genes, which are able to limit vascular inflammation and directly protect against the circulating toxic products of rbc hemolysis (5). Reduction of Keap1 activity in SCD mice by genetic mutation results in Nrf2 activation, decreased inflammation, and tissue damage and demonstrates that cytoprotection by Nrf2 is beneficial in SCD (28). In the present study, we further investigated the expression of cytoprotective proteins controlled by Nrf2, including heme oxygenase-1 (HO-1), ferritin, haptoglobin, and hemopexin, all of which are directly relevant to mitigation of the toxic effects of intravascular hemolysis observed in SCD by metabolizing free Hb, hemin, and iron.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, clinical trials of NRF2 activators have been conducted. For example, studies have shown that the activation of NRF2 exerts cytoprotective effects by enhancing anti-inflammatory and/or antioxidative stress responses in animal models of respiratory disease [5,6], diabetes mellitus [7,8], sickle-cell disease [9] and endotoxin shock [10]. Additionally, phase-3 clinical trials (e.g., the DEFINE and CONFIRM studies) reported that the NRF2 activator dimethyl fumarate (DMF) suppresses the progression and recurrence of multiple sclerosis, which is a progressive neurodegenerative disease caused by ROS-mediated demyelination [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…(5) Recent studies demonstrated that activation of Nrf2 ameliorates the ROS mediated inflammation and tissue damage in SCD by expression of antioxidant enzymes. (6) Although excessive ROS is linked to the hemolysis of red blood cells (RBCs) in SCD and other hemolytic diseases,(7) identifying the primary source and removal mechanisms of ROS are critical steps towards mitigating the hemolytic processes in SCD. ROS production in RBCs of patients with sickle cell disease is due, at least in part, to factors such as sickle hemoglobin auto-oxidation, the Fenton reaction, low levels of antioxidants such as selenium and GPx-1(8) and mediated via an increased activity of NADPH oxidase.…”
Section: Introductionmentioning
confidence: 99%